Entandophragma angolense (WELW) CDC GUM AS A NOVEL BINDER AND MUCOADHESIVE COMPONENT IN ORAL TABLETS (2013)
Mucoadhesive drug delivery systems are designed to prolong drug retention, thus offering advantages over conventional dosages through reduced dosage regimen and improved patient compliance. Natural polymers have gained importance over synthetic materials as excipients in such systems because they are less expensive, biocompatible and biodegradable. Entandophragma angolense gum (ENTA) is used in traditional medicine as a febrifuge, but its excipient properties have not been exploited. This study was carried out to evaluate ENTA as a novel polymer-binder and mucoadhesive component in oral tablets. Entandophragma angolense gum, obtained as dried exudates from the incised trunk of the tree, was characterised using material properties, rheological studies, Fourier-Transform Infrared spectrometer and X-ray diffractometer. Tablets were prepared by Wet Granulation (WG) and Direct Compression (DC) techniques using 2.5 - 10.0 %w/w polymer as binder and 60.0 - 90.0 %w/w polymer as matrix system for controlled release tablets containing ENTA (or official gelatin or hydroxypropylcellulose) with chlorpheniramine maleate (CPM) and ibuprofen as model drugs. Compressional characteristics of the tablets were determined using density measurements, and the Heckel and Kawakita plots. Mechanical and release properties of the tablet formulations were determined by standard methods. Mucoadhesive time (MT) of the tablets were determined ex-vivo in phosphate buffer (pH 7.4) and 0.1M hydrochloric acid (HCl, pH 1.2) using the rotating cylinder method containing excised pig ileum. Data were analysed using descriptive statistics, ANOVA and regression at p = 0.05. The ENTA consisted of irregularly shaped particles with a swelling index of 51.3 %. Rheological studies showed that the final viscosity of 5.0 %w/v ENTA was 258.17 poise. The gum contained hydroxyl groups and was amorphous with some degree of crystallinity. When used as a binder, the ranking of yield pressure was hydroxypropylcellulose > ENTA > gelatin, while the ranking was the reverse for plasticity index. Tablets formulated by WG had higher Tensile Strength (TS) and lower Brittle Fracture Index (BFI) and friability. The ranking of TS was hydroxypropylcellulose > ENTA > gelatin, while those of BFI and friability were the reverse. There was strong correlation(r > 0.98) between binder concentration and dissolution times. When used as polymer for controlled release matrices, the TS increased with binder concentration with tablets prepared by DC technique giving better release profiles than WG technique. The ranking of the disintegration and dissolution times was hydroxypropylcellulose > ENTA > gelatin (p < 0.05). The MT increased with polymer concentration with ibuprofen matrices showing significantly higher MT values than CPM matrices. Generally, the tablets adhered longer in 0.1M HCl, with a ranking of hydroxypropylcellulose (313.00 ± 0.18mins) > ENTA (300.01 ± 0.06mins) > gelatin (207.03 ± 0.11 mins). The polymer matrices provided zero-order drug release for over 14 hours. Entandophragma angolense gum could serve as an alternative binder to official polymers when high mechanical strength is desired. The gum could also serve as a mucoadhesive component in the controlled release of compressed tablets and matrices.